Affine object tracking with kernel-based spatial-color representation - Haihong Zhang; Weimin Huang; Zhiyong Huang; Liyuan Li (2005 IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR'05), 2005)
This paper presents a new visual tracking method that can achieve accurate estimation of affine transformation and precise spatial-color representation. The estimation of transformation provides more information than translation for better motion understanding and also helps maintain the precise representation; the precise representation enables tracking objects in highly-cluttered environment. The basis of the method is a kernel-based similarity measure called affine matching that describes the relationship between image regions with respect to affine transformation parameters. Based on the similarity measure, a mathematical solution is derived for estimating the transformation parameters for moving objects in videos. Various experiments have yielded positive results.